Analysis of sustainable spatial structure of cities under the framework of “Economy-Society- Environment”: A case study Beijing-Tianjin-Hebei urban agglomeration - Haonan Chen; Zhi Li; Xiaoning Cui; Mengchao Zhao; Yu Shi; Haiying Lin; Tianqi Zhu (Ecological Indicators)
The sustainable development of cities is a critical concern and pivotal for the well-being of future generations. Achieving this necessitates a thorough analysis of the spatial dynamics within urban agglomerations, coupled with a comprehensive examination of the factors influencing urban sustainability. Despite existing research efforts, there remains a notable gap in addressing the impact of inter-city interactions on urban sustainability. To address this gap, this study analyzes 17 sustainable development goals for each city within the Beijing-Tianjin-Hebei Urban Agglomeration (JJJUA), utilizing the Economic-Social-Environment (ESE) framework. Furthermore, employing the Random Forest algorithm, this study quantifies the influence of the ESE framework on urban sustainable development. The findings reveal that the core functional area of JJJUA exhibits superior ESE synergies. In contrast, the northwestern region, designated as the Ecological Cultivation Area, demonstrates stronger environmental sustainability albeit with less economic and social cohesion. Conversely, the eastern (Coastal Development Area) and southern (Industrial Expansion Area) parts exhibit higher levels of social and economic sustainability. Improving transportation accessibility and infrastructure development is conducive to promoting economic sustainability; while fortifying the social welfare system advances social sustainability. Additionally, bolstering environmental protection measures serves to promote environmental sustainability.